Implementation of International Conventions on the Participation of National Communities in Creation of TV Broadcasting (on the example - Podkydysheva, Yuliia (Mediaforum : Analytics, Forecasts, Information Management, 2023)
Based on the analysis of international legal standards, the article investigates the possibilities and conditions of television sets in the context of cove-rage of the life of national minorities in Ukraine on the example of the Chernivtsi and Zakarpattia regions. The author concludes: research on television coverage of the activities of national minorities is an indicator of the balance of local, state and international political interests. In the context of the information war aimed at manipulating the image of Ukraine in the context of its positioning as a State that infringes on the right of ethnic communities to express themselves in their own language, the realization of the rights of communities to create content becomes particularly important: it is also about the influence on the work of Ukraine to improve the legislation in the context of the European integration. The article emphasizes the priority of creation and financial support of TV platforms where representatives of national communities can produce and distribute media content that does not contradict the national interests of Ukraine.